STUDY OF CEREBRAL SALT WASTING SYNDROME AND SYNDROME OF INAPPROPRIATE ANTIDIURETIC HORMONE SECRETION AMONG STROKE PATIENTS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Hyponatremia is a common electrolyte abnormality in patients with Stroke and is associated with increased morbidity and poor neurological outcomes. Syndrome of inappropriate antidiuretic hormone secretion (SIADH) and cerebral salt wasting syndrome (CSWS) are the major causes of hyponatremia in stroke patients. Early differentiation between these conditions is important because their management differs significantly. This study aimed to evaluate the occurrence of SIADH and CSWS among patients with stroke. Methodology: This hospital-based observational study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from January 2025 to December 2026. Fifty patients with clinically and radiologically confirmed stroke were included in the study. Detailed clinical evaluation, biochemical investigations, serum sodium levels, urine sodium, and assessment of volume status were performed. Data were analyzed using SPSS version 20.0. Chi-square test and Student’s t-test were used for statistical analysis, with p